2015
DOI: 10.1007/s00787-015-0731-3
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing ADHD phenotypic heterogeneity: searching for neurobiological underpinnings of the restrictive inattentive phenotype

Abstract: During the process of developing the DSM-5, a new phenotype of ADHD was proposed-the ADHD restrictive inattentive presentation (ADHD-RI), describing subjects with high endorsement of inattentive symptoms and a low level of hyperactivity. However, this phenotype was not included in the DSM-5 because of the lack of robust neurobiological data. We aimed to assess the specific neurobiological underpinnings of individuals presenting ADHD-RI. We compared a sample of 301 subjects (101 ADHD-Combined; 50 ADHD-RI; 50 AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
1
9
1
Order By: Relevance
“…A child who struggles with executive functioning may respond in a haphazard manner, pay poor attention to detail, and not self-regulate performance well (e.g., have poor pacing and not switch well between symbols), leading to slow and/or inaccurate performance. These results are consistent with past findings on psychomotor slowing in ADHD in that it may be specific to neurodevelopmental impulsivity and less commonly found when comparing other psychiatric groups (i.e., mood, anxiety and oppositional defiant disorders) to controls (Mayes & Calhoun, 2007; Sabri et al, 2016; Walker, Shores, Trollor, Lee & Sachdev, 2000). Alternatively, given that Coding always was administered prior to Coding Copy following the WISC Integrated manual’s procedures, it is possible that children with more efficient working memory were able to encode the symbols better during Coding and, thus, perform better on Coding Copy.…”
Section: Discussionsupporting
confidence: 92%
“…A child who struggles with executive functioning may respond in a haphazard manner, pay poor attention to detail, and not self-regulate performance well (e.g., have poor pacing and not switch well between symbols), leading to slow and/or inaccurate performance. These results are consistent with past findings on psychomotor slowing in ADHD in that it may be specific to neurodevelopmental impulsivity and less commonly found when comparing other psychiatric groups (i.e., mood, anxiety and oppositional defiant disorders) to controls (Mayes & Calhoun, 2007; Sabri et al, 2016; Walker, Shores, Trollor, Lee & Sachdev, 2000). Alternatively, given that Coding always was administered prior to Coding Copy following the WISC Integrated manual’s procedures, it is possible that children with more efficient working memory were able to encode the symbols better during Coding and, thus, perform better on Coding Copy.…”
Section: Discussionsupporting
confidence: 92%
“…Task-based studies investigating either the ADHD-C or the ADHD-I subtype, relative to controls, also provide supporting evidence for these aberrant functional differences in ADHD subtypes. Greater activation in the temporo–occipital and posterior brain regions were found in the hypothesized restrictive inattentive ADHD (ADHD-RI) type (Ercan et al, 2016b ) and decreased activation in ADHD-I, relative to ADHD-C, in regions involving the cingulo–frontal–parietal attention (Orinstein and Stevens, 2014 ) has been reported. Studies examining the ADHD-C type showed task-dependent activation differences in regions involving the parietal, temporal lobes and basal ganglia, in line with the findings suggestive of fronto–striatal–thalamic deficits (Silk et al, 2005 ; Vaidya et al, 2005 ; Smith et al, 2006 , 2008 ; Tamm et al, 2006 ; Rubia et al, 2007 ; Stevens et al, 2007 ; Vance et al, 2007 ; Fassbender et al, 2009 ; Iannaccone et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, research suggests that atomoxetine reduces SCT symptoms in youth with ADHD [41,42], which aligns with other studies indicating atomoxetine to be effective for youth with ADHD and co-occurring internalizing symptoms [43,44] These findings together suggest that SCT as a possible specifier among children with ADHD is an area worth further examination, particularly if an SCT specifier can inform treatment decisions. In addition, there has recently been some renewed interest in a possible ADHD restrictive inattentive presentation [45], and children with this phenotype may have a different neuropsychological and attentional profile than other children with ADHD, as well as different brain functioning and genetic markers (e.g., presence of the DRD4-7 repeat allele) [46,47]. Integrating SCT within studies of ADHD restrictive inattentive presentation would be advantageous as part of overall efforts to better understand and categorize the phenotypic heterogeneity of ADHD.…”
Section: Key Considerations For Examining Sct Within the Dsm Frameworkmentioning
confidence: 99%